Institutional engineering and political accountability in Indonesia, Thailand and the Philippines - Ziegenhain, Patrick (ISEAS Publishing, 2015)
Political accountability is a crucial element of any democracy since it is a safeguard against power abuse and corruption, both urgent problems of many political systems in Southeast Asia. Based on social science theories, the author analyses from a comparative perspective the ways institutional engineering concerning different dimensions of political accountability influenced the quality of democracy in Indonesia, Thailand and the Philippines. By highlighting the successes and shortcomings, this book evaluates the degree these institutional reforms resulted in the deepening, stagnation, or regression of the respective democratization processes in these three Southeast Asian countries.